2013
DOI: 10.4085/1062-6050-48.4.11
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Interventions for Increasing Ankle Dorsiflexion After Ankle Sprain: A Systematic Review

Abstract: Static-stretching intervention as a part of standardized care yielded the strongest effects on dorsiflexion after acute ankle sprains. The existing evidence suggests that clinicians need to consider what may be the limiting factor of ankle dorsiflexion to select the most appropriate treatments and interventions. Investigators should examine the relationship between improvements in dorsiflexion and patient progress using measures of patient self-reported functional outcome after therapeutic interventions to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
75
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(82 citation statements)
references
References 45 publications
1
75
1
5
Order By: Relevance
“…There was a significant amount of overlap between the reviews regarding the injury type of interest, with 15 reviews being classified as investigating treatment strategies for both acute ankle sprain and CAI 14 17 19 24 28 32 34 37 41 43 45 50 52 53 60. Twenty reviews investigated treatment strategies for acute ankle sprain specifically 18 21–23 26 27 29–31 39 40 44 46–49 54 55 58 61.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a significant amount of overlap between the reviews regarding the injury type of interest, with 15 reviews being classified as investigating treatment strategies for both acute ankle sprain and CAI 14 17 19 24 28 32 34 37 41 43 45 50 52 53 60. Twenty reviews investigated treatment strategies for acute ankle sprain specifically 18 21–23 26 27 29–31 39 40 44 46–49 54 55 58 61.…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen systematic reviews evaluated a physiotherapeutic intervention for the treatment of acute ankle sprain14 17 19 23 29 31 32 39 41 44 45 50 52 53 58 60 61 95 (quality range=2–10), which themselves included 118 individual reports were included on removal of papers duplicated between each review. The two main kinds of physiotherapeutic intervention evaluated were exercise therapy and manual therapy.…”
Section: Resultsmentioning
confidence: 99%
“…To assess stretching effects, we calculated the Cohen d using mean 6 standard deviation for the preintervention and postintervention data. 24,32 Cohen d values .0.8 indicated a strong effect, values .0.4 to 0.8 were regarded as moderate, and values 0.4 were rated as weak. 24,32 Independent t tests were used to compare initial differences in the ankle DFROM of the static-stretching and SSS groups.…”
Section: Resultsmentioning
confidence: 99%
“…24 However, SSS can be applied independently in the dynamic-lunge position using talar stabilization to improve ankle DFROM. 1,5,15 Thus, the aim of our study was to determine the effects of SSS on improvements in active DFROM (ADFROM), passive DFROM (PDFROM), and the lunge angle compared with static stretching.…”
mentioning
confidence: 99%
“…Basnett et al [79] recently showed a positive correlation between dorsiflexion range of motion and dynamic balance during the SEBT. A systematic review [80] recently showed improvement in dorsiflexion range of motion with static stretching but recommends clinicians be thorough in determining the cause of the dorsiflexion deficit. Anterior positional faults of the talus within the talocrural joint may result from an inversion mechanism due to the insertions of the anterior talofibular ligament [81].…”
Section: Rehabilitationmentioning
confidence: 99%